Clinical Presentation, Management, and Outcomes of Patients With Brain Abscess due to Nocardia Species. (7th April 2021) - Corsini Campioli, Cristina; Castillo Almeida, Natalia E; O'Horo, John C; Challener, Douglas; Go, John Raymond; DeSimone, Daniel C; Sohail, M Rizwan
Abstract: Background: Nocardial brain abscesses are rare, and published literature describing brain abscesses due to Nocardia species is limited to individual case reports or small series. We report one of the largest contemporary retrospective studies describing risk factors, diagnostic evaluation, management, and outcomes of nocardial brain abscess. Methods: Retrospective review of all adults with brain abscess due to culture-confirmed Nocardia species at our institution between January 1, 2009, and June 30, 2020. Results: Overall, 24 patients had nocardial brain abscesses during the study period. The median age at presentation was 64 years, and 62.5% were immunocompromised. Pulmonary and cutaneous infections were the most common primary sites of nocardial infection. All 24 patients had magnetic resonance imaging performed, and the frontal lobe was the most commonly involved. The most common organism isolated was Nocardia farcinica, followed by Nocardia wallacei and Nocardia cyriacigeorgica . Thirteen patients were managed with antimicrobial therapy alone, while 11 had both medical and surgical management. In all patients, dual therapy was recommended for the initial 6 weeks of treatment, and 22 patients received at least 1 oral agent as part of their final antibiotic regimen, predominantly trimethoprim-sulfamethoxazole and linezolid. Fourteen patients achieved complete clinical and radiographic resolution of infection. Conclusions: Nocardia is an important cause of brain abscess in the immunocompromised host. Early diagnostic and therapeutic aspiration may help health care providers confirm the diagnosis, choose an appropriate antimicrobial regimen, and achieve source control. Abstract : Nocardia is an important cause of brain abscess in the immunocompromised host. Early diagnostic and therapeutic aspiration may help confirm the diagnosis, choose an appropriate antimicrobial regimen, and achieve source control to attain a clinical and radiographic resolution of infection.